2003
DOI: 10.1152/ajpcell.00590.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential relaxing responses to particulate or soluble guanylyl cyclase activation on endothelial cells: a mechanism dependent on PKG-Iα activation by NO/cGMP

Abstract: cGMP is generated in endothelial cells after stimulation of soluble guanylyl cyclase (sGC) by nitric oxide (NO) or of particulate guanylyl cyclase (pGC) by natriuretic peptides (NP). We examined whether localized increases in cytosolic cGMP have distinct regulatory roles on the contraction induced by H2O2 treatment in human umbilical vein endothelial cells. cGMP concentrations and temporal dynamics were different upon NO stimulation of sGC or C-type NP (CNP) activation of pGC and did not correlate with their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
(41 reference statements)
2
28
0
1
Order By: Relevance
“…10). This suggested compartmentalization of cGMP signaling, an emerging theme in multiple cell types (14,15,30,31,36). The observation that 8-pCPT-cGMP did not mimic the effect of pGC activation suggested that a cGMP-sensitive PDE was again involved rather than PKG I .…”
Section: Discussionmentioning
confidence: 99%
“…10). This suggested compartmentalization of cGMP signaling, an emerging theme in multiple cell types (14,15,30,31,36). The observation that 8-pCPT-cGMP did not mimic the effect of pGC activation suggested that a cGMP-sensitive PDE was again involved rather than PKG I .…”
Section: Discussionmentioning
confidence: 99%
“…Scoparone also elevated the basal level of cGMP, which results in decreased phosphorylation of myosin light chain, then dilatation. 40,41) NO produced by the eNOS activation can dilate the vessel wall and scoparone may potentiate this vasodilative effect of NO. Paradoxically, scoparone has an inhibitory effect on NO generation through iNOS activation under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic GMP was extracted from BAEC following published methods 26 ; cGMP production in each sample was measured by radioimmunoassay and corrected by protein amount (please see Supplemental data).…”
Section: Measurement Of Cyclic Gmpmentioning
confidence: 99%